The seventh scroll - Smith, Wilbur A. (New York : St. Martin's Paperbacks, 1996)
In Ethiopia, the search for a pharaoh's treasure by Royan Al Simma, a beautiful Egyptologist. When her map is stolen and her husband murdered by a German villain, Royan enrolls the services of an adventurous English nobleman. A dangerous expedition as the tomb is booby-trapped.
Keywords: Egypt -- Antiquities -- Collection and preservation -- Fiction; Action and adventure fiction